PERILAKU MAHASISWA KEDOKTERAN TERHADAP GAMBAR BAHAYA MEROKOK PADA KEMASAN ROKOK (STUDI KASUS FAKULTAS KEDOKTERAN UR DAN FAKULTAS KEDOKTERAN ABDURRAB DI PEKANBARU) - Indah, Rahayu; Hidir, Achmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Research conducted in April 2015 to June 2015 in Faculty of MedicineUR and Faculty of Medicine Abdurrab in Pekanbaru it aims to find out how thebehavior of medical students who smoke against the dangers of smoking imageson cigarette packs. The method used is qualitative method with descriptive type(Deskriptive Research). Informants used are medical students who smoke.Collect observational data, which then obtained data analyzed qualitatively.The results showed that the image of smoking on cigarette packs do not have animpact on their. Medical of students respond to usual against the picture, so theuse of cigarette consumption and still no change. And also their responsetowards the phenomenon of smoke that gets bigger it’s also considered normalbecause according to them the smoking already familiar. According to they ofsmoking can eliminate busy and cozy effect when consumption.Keywords: Smoking student, Response, and Behavior